Towards Selective Syntheses of Octadienylethers from the Butadiene Palladium‐catalyzed Telomerization with Polyols in Aqueous Biphasic Medium. Issue 6 (27th February 2019) - Drelon, Mathieu; Mérel, Delphine S.; Mortreux, André; Suisse, Isabelle; Sauthier, Mathieu
Abstract: The palladium catalyzed telomerization of butadiene with polyols has been efficiently performed under aqueous and biphasic medium leading to the corresponding octadienylethers. Depending on the choice of the organic co‐solvent and nature of the catalyst employed to promote the reaction, mono‐ to fully substituted ethers could be obtained with high selectivities and yields. Particularly, pentaerythritol was telomerized for the first time allowing the selective synthesis of the corresponding monotelomers by using methylethylketone as organic co‐solvent and the water soluble ligand TPPTS associated to a simple palladium precursor. Polyethers of sorbitol could be efficiently obtained by using a mixture of TPPTS and PPh3 ligands. Abstract : As seen on the Telo ! The palladium‐catalyzed telomerization of butadiene with polyols has been efficiently performed under aqueous and biphasic medium. Particularly, pentaerythritol was telomerized for the first time allowing the selective synthesis of the corresponding monotelomers.